STRATEGI SI PELIT (SISTEM INFORMASI PELAYANAN LABORATORIUM TERPADU) SEBAGAI OPTIMALISASI PELAYANAN PUBLIK DI POLTEKKES KEMENKES BANJARMASIN - Maulida Yanti; Suryanti; Redho Rosehan Anwar (Rena Cipta Mandiri, 2025)
Laboratories in educational institutions are important facilities that support the processes of education, research, and community service. An integrated information system is necessary for effective laboratory management so that practical activities, administration, and equipment use can be carried out properly. The purpose of this study was to produce a digital innovation for laboratory services at the Banjarmasin Ministry of Health Polytechnic, namely the Si Pelit Application, which is a Content Management System (CMS). This research was conducted using a real-world research approach based on theory. The five stages of research were: (1) preparation and instrument development; (2) pre-research; (3) licensing; (4) data collection; and (5) instrument processing and evaluation. Data were collected from 60 students randomly selected from the Faculty of Midwifery and Dental Health. The Si Pelit Application uses a community satisfaction index (CSI) to measure user satisfaction levels. The results of the study show that the average user perception is 3.435 and the IKM conversion value is 85.875, which is in the B (Good) quality interval. This indicates that students consider the Si Pelit application to be effective and efficient in supporting laboratory activities, helping them gain access to information about tools, and improving their practical skills. It is assessed that this application can be used for the digitization of laboratory services that are innovative, professional, and adaptive to developments in information technology in the field of health education.